Polyeideia : the Iambi of Callimachus and the archaic Iambic tradition - Acosta-Hughes, Benjamin, 1960- (Hellenistic culture and society, 2002)
This book provides a new literary treatment of an often-overlooked collection of fragmentary poems from the third century B.C.E. Alexandrian poet Callimachus. Callimachus' Iambi form a collection of thirteen poems, which rework archaic Greek iambography and look forward to Roman satire and other genres, especially to such collections as Horace's Epodes.